Global estimates on the number of people blind or visually impaired by diabetic retinopathy: a meta-analysis from 2000 to 2020 - Curran, Katie; Peto, Tunde; Jonas, Jost B.; Bärnighausen, Till (Eye, 2024)
To estimate global and regional trends from 2000 to 2020 of the number of persons visually impaired by diabetic retinopathy and their proportion of the total number of vision-impaired individuals.
Online veröffentlicht: 27. Juni 2024
Mitglieder der Vision Loss Expert Group of the Global Burden of Disease Study: Katie Curran, Tunde Peto, Jost B. Jonas, David Friedman, Judy E. Kim, Janet Leasher, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Alessandro Arrigo, Nicolas Leveziel, Serge Resnikoff, Hugh R. Taylor, Tabassom Sedighi, Seth Flaxman, Mukkharram M. Bikbov, Tasanee Braithwaite, Alain Bron, Ching-Yu Cheng, Monte A. Del Monte, Joshua R. Ehrlich, João M. Furtado, Gus Gazzard, M. Elizabeth Hartnett, Rim Kahloun, John H. Kempen, Moncef Khairallah, Rohit C. Khanna, Van Charles Lansingh, Kovin S. Naidoo, Vinay Nangia, Michal Nowak, Konrad Pesudovs, Pradeep Ramulu, Fotis Topouzis, Mitiadis Tsilimbaris, Ya Xing Wang, Ningli Wang and Rupert R.A. Bourne
Mitglieder der The GBD 2019 Blindness and Vision Impairment Collaborators: Katie Curran, Tunde Peto, Rupert Bourne, Janet L. Leasher, Jost B. Jonas, Tabassom Sedighi, David S. Friedman, Judy E. Kim, Arthur G. Fernandes, Bright Opoku Ahinkorah, Hamid Ahmadieh Ayman Ahmed, Ahmad Samir Alfaar, Louay Almidani, Hubert Amu, Sofia Androudi, Jalal Arabloo, Aleksandr Y. Aravkin, Mulu Tiruneh Asemu, Ahmed Y. Azzam, Nayereh Baghcheghi, Freddie Bailey, Mehmet Firat Baran, Mainak Bardhan, Till Winfried Bärnighausen, Amadou Barrow, Pankaj Bhardwaj, Mukharram Bikbov, Tasanee Braithwaite, Paul Svitil Briant, Katrin Burkart, Luis Alberto Cámera, Kaleb Coberly, Omid Dadras, Xiaochen Dai, Amin Dehghan, Berecha Hundessa Demessa, Mengistie Diress, Thanh Chi Do, Thao Huynh Phuong Do, Klara Georgieva Dokova, Bruce B. Duncan, Michael Ekholuenetale, Muhammed Elhadi, Mohammad Hassan Emamian, Mehdi Emamverdi, Hossein Farrokhpour, Ali Fatehizadeh, Lorenzo Ferro Desideri, João M. Furtado, Mesfin Gebrehiwot, Fariba Ghassemi, Mesay Dechasa Gudeta, Sapna Gupta, Veer Bala Gupta, Vivek Kumar Gupta, Billy Randall Hammond, Mehdi Harorani, Hamidreza Hasani, Golnaz Heidari, Mehdi Hosseinzadeh, John J. Huang, Sheikh Mohammed Shariful Islam, Nilofer Javadi, Aida Jimenez-Corona, Mohammad Jokar, Charity Ehimwenma Joshua, Vidya Kadashetti, Himal Kandel, Hengameh Kasraei, Rimple Jeet Kaur, Sudarshan Khanal, Zahra Khorrami, Hamid Reza Koohestani, Kewal Krishan, Stephen S. Lim, Mohammed Magdy Abd El Razek, Vahid Mansouri, Andrea Maugeri, Tomislav Mestrovic, Awoke Misganaw, Ali H. Mokdad, Hamed Momeni-Moghaddam, Sara Momtazmanesh, Christopher J.L. Murray, Hadush Negash, Uchechukwu Levi Osuagwu, Shahina Pardhan, Jay Patel, Shrikant Pawar, Ionela-Roxana Petcu, Hoang Tran Pham, Mohsen Pourazizi, Ibrahim Qattea, Mosiur Rahman, Umar Saeed, Amirhossein Sahebkar, Mohammad Amin Salehi, Maryam Shayan, Aminu Shittu, Jaimie D. Steinmetz, Yao Tan, Hugh R. Taylor, Fotis Topouzis, Aristidis Tsatsakis, Muhammad Umair, Theo Vos, Hong Xiao, Yuyi You, Mikhail Sergeevich Zastrozhin, Zhi-Jiang Zhang and Peng Zheng
Gesehen am 11.02.2025